2003
DOI: 10.1097/00001756-200312020-00002
|View full text |Cite
|
Sign up to set email alerts
|

Anterior ectosylvian cortical projections to the rostral suprasylvian multisensory zone in cat

Abstract: Recent studies have shown that the anterior ectosylvian sulcal cortex (AESc) and the rostral suprasylvian sulcal cortex (RSSSc) of the cat play integral roles in behavioral and collicular responses to multisensory stimuli. However, substantially more multisensory superior colliculus (SC) neurons are affected by blockade of the AESc than the RSSSc. Although both cortical regions project directly to the SC, a possible explanation for this differential effect is that the AESc may also relay an indirect corticotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The somatosensory, auditory and multisensory response properties as well as the sulcal location of the MRSS correlate closely with that recently described for cat rostral suprasylvian sulcal cortices (Monteiro et al 2003; Clemo et al 2007). Furthermore, if general homologies with cat somatosensory cortices can be assumed, MRSS probably could not be regarded as either the second (SII) and fourth (SIV) somatosensory areas.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The somatosensory, auditory and multisensory response properties as well as the sulcal location of the MRSS correlate closely with that recently described for cat rostral suprasylvian sulcal cortices (Monteiro et al 2003; Clemo et al 2007). Furthermore, if general homologies with cat somatosensory cortices can be assumed, MRSS probably could not be regarded as either the second (SII) and fourth (SIV) somatosensory areas.…”
Section: Discussionsupporting
confidence: 84%
“…A similar region of the rostral suprasylvian sulcus in the cat is included in the traditionally defined multisensory “suprasylvian fringe” (Heath and Jones 1971a, b) that separates auditory (AAF: Reale and Imig 1980) from somatosensory gyral cortices (area 5: Avendano et al 1988; Graybiel 1972; Hassler and Muhs-Clement 1964) and the third somatosensory region, SIII (Dykes et al 1977; Tanji et al 1978). Recent examination of the lateral bank of the suprasylvian sulcus in cat, where it abuts the auditory AFF, has revealed that there are transitions between the auditory and somatosensory representations that contain multisensory (auditory–somatosensory) neurons (Clemo et al 2007; Monteiro et al 2003). In the ferret, a preliminary examination of the lateral bank of the rostral suprasylvian sulcus suggests that it is a site of multisensory convergence (Keniston et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For multisensory cortex, the primary recipient layers for multiple sensory information appear to be layers 2/3 (see also Clemo et al,2007,2008; Dehner et al,2004; Meredith et al,2006; Monteiro et al,2003), which largely receive projections from other cortical areas. It is of note that a current‐source density analysis of the monkey multisensory cortex located in the superior temporal sulcal cortex (STS) described initial current sinks for separate visual, auditory, and somatosensory responses to be centered on layer 4 (and lower layer 3; Schroeder and Foxe,2002).…”
Section: Discussionmentioning
confidence: 99%
“…In monkeys, multisensory neurons in the superior temporal sulcal region were demonstrated to cluster spatially (Dahl et al,2009), and the laminar distribution of separate visual, auditory, and somatosensory activation of this same cortical region has been examined (Schroeder and Foxe,2002). On the other hand, recent neuroanatomical studies of cat multisensory cortices have demonstrated a strong preference for corticocortical inputs to terminate within layers 2/3 (Clemo et al,2007,2008; Dehner et al,2004; Meredith et al,2006; Monteiro et al,2003; for review see Clemo et al,2011), but correlations with laminar multisensory properties were not made. Altogether, these few observations indicate that the laminar basis for multisensory processing is largely unexplored.…”
mentioning
confidence: 99%
“…For example, in cats, there is the rostral lateral suprasylvian sulcus multisensory area (r-LS, [38]; AESc [39]) that extends medially onto the suprasylvian gyrus; and in rats and mice, there are the V1-recipient and S-I-recipient rostrolateral (RL) and anterior area(A). As in humans and non-human primates, these areas lie at the border between unimodal visual and somatosensory areas, they are anterior and superior to most other extrastriate visual areas, and they are distinctly medial to the representation of the face in primary somatosensory cortex.…”
Section: Comparative Anatomy Of Parietal Areasmentioning
confidence: 99%